Power transformer condition monitoring and diagnosis - Abu-Siada, Ahmed (IET energy engineering series ;, 2018)
The following topics are dealt with: power transformer; condition monitoring; dissolved gas analysis; partial discharges; moisture analysis; paper; thermal ageing and mechanical oscillations.